Optimization of bioactivity and antibacterial properties of porous Ti-based bulk metallic glass through chemical treatment. (1st May 2023) - Du, Peng; Xiang, Tao; Yang, Xinxin; Xie, Guoqiang
Abstract: Porous Ti–Zr–Cu–Pd–Sn bulk metallic glass (BMG) with bone-like mechanical properties, created using the one-step spark plasma sintering (SPS) process, offers a significant deal of potential for usage as orthopedic biomaterials. However, due to a lack of bioactivity and an inability to manage the antibacterial ability, its therapeutic usefulness is severely limited. Here, a bioactive titanate layer was synthesized in situ on the inner and outer surfaces of porous Ti-based BMG by a chemical treatment method. This research not only significantly confers a bone-bonding capability to porous Ti-based BMG, but it also achieves the modulation of Cu 2+ ion release rate, substantially lowering the potential biological toxicity of porous Ti-based BMG. In parallel, a thorough analysis of the structure, morphology, mechanical characteristics, corrosion resistance, and antibacterial properties of the porous BMG before and after chemical treatment was conducted. It is anticipated that this discovery will assist to further advance the use of porous Ti-based BMG as orthopedic biomaterials. Graphical abstract: Image 1